Business Cycles in an Oil Economy: Lessons from Norway - Drago Bergholt; Vegard Høghaug Larsen (Norges Bank, 2016)
The recent oil price fall has created concern among policy makers regarding the consequences of terms of trade shocks for resource-rich countries. This concern is not a minor one - the world's commodity exporters combined are responsible for 15-20% of global value added. We estimate a two-country New Keynesian model in order to quantify the importance of oil price shocks for Norway - a large, prototype petroleum exporter. Domestic supply chains link mainland (non-oil) Norway to the off-shore oil industry, while fiscal authorities accumulate income in a sovereign wealth fund. Oil prices and the international business cycle are jointly determined abroad. These features allow us to disentangle the structural sources of oil price fluctuations, and how they affect mainland Norway. The estimated model provides three important results: First, pass-through from oil prices to the oil exporter implies up to 20% higher business cycle volatility. Second, the majority of spillover effects stem from non-oil disturbances such as innovations in international investment efficiency. Conventional oil market shocks, in contrast, explain at most 10% of the Norwegian business cycle. Third, the prevailing fiscal regime provides substantial protection against external shocks while domestic supply linkages make the oil exporter more exposed.
hdl:11250/2495712
Keywords: 330